Commentary: Recesses of the Young Poetic Mind (LEARNing Landscapes, 2010)
In this interview young poet Sophie Hillcoat shares her story of how she began writing poetry during recess. She talks of her sources of inspiration and the important role that her friends play in contributing to her creative process. She has suggestions for young people who would like to start writing poetry as well as for teachers who teach poetry. Finally, she reads one of her poems.
Keywords: poetry; interview; inspiration; teaching poetry